Equality of Opportunities and Fiscal Incidence in Cote d'Ivoire - Abras, Ana; Cuesta, Jose; Hoyos, Alejandro; Narayan, Ambar (World Bank, Washington, DC, 2012)
This study analyzes opportunities for children in Cote d'Ivoire, where opportunities refer to access to basic services and goods that improve the likelihood of a child maximizing his or her human potential. The principle that guides this analysis is one of equality of opportunity, which is that a child's circumstances at birth should not determine his or her access to opportunities. The analysis computes the Human Opportunity Index, which measures the extent to which access to basic services is universal and evenly distributed among children of different circumstances. Opportunities are limited in Cote d'Ivoire, despite some improvements in access to electricity and timely access to primary education. Otherwise, trends on access remain stagnant. Scale effects (variations across the board) are behind these trends, with little improvement observed from equalizing interventions. Circumstances such as region and household head characteristics affect a child's access to opportunities, while household incomes and a child's gender and ethnicity play a relatively small role in access differentials. Public spending on education opportunities is shown to be regressive and pro-rich, especially when analyzed across the distribution of circumstances rather than acroos income level.The groups of children that are particularly behind in terms of educational opportunities are those whose household heads lack primary education and reside in rural areas. Closing the enrollment gap of these children should be a priority for targeted educational interventions. However, improving opportunities may require more than a single type of intervention: opportunities with low coverage may need to be scaled up, while those with large inequalities of access may require equalizing interventions.